2008
DOI: 10.2169/internalmedicine.47.0475
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneovenous Shunting for Intractable Chylous Ascites Complicated with Lymphangioleiomyomatosis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…Peritoneal disease, including Lymphangioleiomyomatosis (LAM) and peritoneal mesothelioma was also associated with higher incidence of occlusion. This is similar to previous case reports in which the shunt occluded in three out of four patients (75%) with LAM (21, 28, 32, 33). Therefore, when counseling patients with LAM, they should be advised that they are at increased risk for shunt malfunction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Peritoneal disease, including Lymphangioleiomyomatosis (LAM) and peritoneal mesothelioma was also associated with higher incidence of occlusion. This is similar to previous case reports in which the shunt occluded in three out of four patients (75%) with LAM (21, 28, 32, 33). Therefore, when counseling patients with LAM, they should be advised that they are at increased risk for shunt malfunction.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, returning the chylous fluid back into the circulation is actually physiologic, though in shunt patients, the fluid is returning through an artificial conduit. Makino et al , twice infused 1000 ml of CA intravenously after paracentesis in a patient with CA and observed no coagulation abnormality (28). Additionally, in none of the 56 patients reported in the literature has DIC been observed (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Thoracentesis or abdominocentesis also play a role in temporarily relieving symptoms such as dyspnea or distended sensation, but the repeated elimination of large amounts of chyle will result in malnutrition and a secondary immunodeficient state due to loss of nutrients and lymphocytes. 78 Diuretics seem to provide variable benefit in controlling the amount of chyle leakage and ameliorating symptoms. A fat-restricted diet alone or with supplementation of medium-chain triglycerides is generally recommended.…”
Section: Clinical Manifestations Related To Lymphatic Involvementsmentioning
confidence: 99%
“…Successful instillation of a peritoneo-venous shunt for intractable chylous ascites has also been reported by several groups. 78,92 Rapamycin, an mTOR inhibitor, is an attractive possibility since constitutively activated mTOR due to the loss of TSC1=TSC2 function is the pathogenic basis of LAM. Sirolimus, a type of rapamycin, has been successfully used for the treatment of TSC-associated diseases including LAM and AML.…”
Section: Clinical Manifestations Related To Lymphatic Involvementsmentioning
confidence: 99%
“…Some studies have reported success rates in the order of 90% with 6 weeks of parenteral feeding and fasting 10. Surgical management includes either open or laparoscopic approach to direct suture ligation of the chyle leakage,1113 or insertion of a peritoneovenous shunt,12 and is typically reserved for cases refractory to maximal medical management.…”
Section: Discussionmentioning
confidence: 99%